Automatic helmet-less biker detection using deep learning - Ratul, Md. Ibrahim; Mohon, Abdul Karim Ibne; Sarker, Md. Reduan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.